La SQRM 1980-2005 : Une première approche historique - Bail, Louise (Les Cahiers de la Société québécoise de recherche en musique, 2020)
En 2005, l’ARMuQ/SQRM fêtait son 25 e anniversaire d’existence. Répondant aux questions de la rédactrice en chef des présents Cahiers , Sylvia L’Écuyer, l’auteure expose d’abord les motifs qui ont poussé les membres fondateurs à créer ce qui s’appelait alors l’Association pour l’avancement de la recherche en musique du Québec (ARMuQ). Cette section est suivie d’un aperçu des différentes phases de l’évolution de l’association. Enfin, dans une troisième section intitulée « Problématiques et souhaits d’avenir », Louise Bail tente de dégager très brièvement les liens que l’ARMuQ/SQRM a développés avec les institutions d’enseignement supérieur et de circonscrire la place que prennent les chercheurs indépendants au sein de l’organisme. Son propos s’emploie à faire ressortir les problèmes particuliers que posent le fonctionnement et l’existence d’une telle association. Enfin, elle propose des réflexions et suggère quelques pistes d’avenir à partir de son implication en tant que membre fondateur, membre régulier et présidente sortante du conseil d’administration. , In 2005, the ARMuQ/SQRM celebrated its twenty-fifth anniversary. Responding to questions from the Cahier’s current Editor-in-Chief, Sylvia L’Écuyer, the author begins by discussing the motives that gave rise to the Association pour l’avancement de la recherche en musique du Québec, as it was then called. This is followed by a survey of the association’s various transformations over the years. In a third section entitled “Problématiques et souhaits d’avenir” (“Challenges and wishes for the future”), Louise Bail describes the ties that bind the ARMuQ/SQRM to post-secondary education institutions, and identifies the role of independent scholars within the organisation. The aim of her study is to discern the particular challenges that the existence and operations of such an association create. Finally, she reflects and advises on the association’s future from the perspective of her own role as founding member, regular member, and past Chair of the Board of Directors.

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Publisher: Circuit, musiques contemporaines
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

Death and Fairy Tale: Queer Autothanatography in Claude Vivier - Kingston, Andrew (differences, 2020)

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound